Understanding Characteristics of Religion within Urban, Rural and Tribal Societies (Indian Journal of Social Science and Literature (IJSSL), 2024)
The individuals, belonging to all communities, i.e. rural, tribal and urban have one of the major goals of bringing about improvements in their overall standards of living. This is regarded as one of the essential goals of individuals, belonging to all occupations, communities and socio-economic backgrounds. The individuals are normally wholeheartedly committed towards achievement of desired goals and objectives. The possessions of strong religious beliefs are regarded as vital. As a consequence, the individuals are able to prepare themselves adequately in carrying out all types of complicated tasks and activities. The individuals reinforce the viewpoint that worshipping the Almighty will be facilitating in putting into operation all types of tasks and activities in a well-organized and regimented manner. Furthermore, individuals will be well-prepared in overcoming all types of setbacks. The characteristics of religion are similar as well as different among individuals, belonging to urban, rural and tribal communities. The individuals need to make sure, they put into operation job duties, which are facilitating in carrying out all types of job duties and responsibilities in a satisfactory manner. Therefore, it is necessary for individuals to acquire an efficient understanding of religion. The main concepts that are taken into account in this research paper are, generation of information regarding characteristics of religion is enriching to individuals in all societies, characteristics of religion within urban, rural and tribal societies and advantages of acquiring an efficient understanding of characteristics of religion.